2017
DOI: 10.1038/s41467-017-01579-0
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent mass transfer caused by vortex induced reconnection in collisionless magnetospheric plasmas

Abstract: Magnetic reconnection is believed to be the main driver to transport solar wind into the Earth’s magnetosphere when the magnetopause features a large magnetic shear. However, even when the magnetic shear is too small for spontaneous reconnection, the Kelvin–Helmholtz instability driven by a super-Alfvénic velocity shear is expected to facilitate the transport. Although previous kinetic simulations have demonstrated that the non-linear vortex flows from the Kelvin–Helmholtz instability gives rise to vortex-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
111
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 53 publications
17
111
1
Order By: Relevance
“…(e.g., τ0.4ωci1 for Wilder et al, ). Reconnection events driven by KH waves in the magnetopause flank have been proposed to contain multiple flux ropes which might support such dynamics (Eriksson et al, ; Nakamura et al, ; Sturner et al, ). Recent observations in sub‐ion scale current sheets have also observed very large parallel electric fields E || ∼5 E 0 (Phan et al, ); this presents a second idea that large reconnection rates may be linked to reconnection at small spatial scales.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…(e.g., τ0.4ωci1 for Wilder et al, ). Reconnection events driven by KH waves in the magnetopause flank have been proposed to contain multiple flux ropes which might support such dynamics (Eriksson et al, ; Nakamura et al, ; Sturner et al, ). Recent observations in sub‐ion scale current sheets have also observed very large parallel electric fields E || ∼5 E 0 (Phan et al, ); this presents a second idea that large reconnection rates may be linked to reconnection at small spatial scales.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Based on a 3D fully kinetic simulation of the same MMS KH event on 8 September 2015, Nakamura, Eriksson, et al () and Nakamura, Hasegawa, et al () conducted a study of plasma turbulence and transport across the flank magnetopause due to the KH instability and vortex‐induced magnetic reconnection. MMS burst observations of ion‐scale reconnection exhausts and electron‐scale dissipation associated with an electron diffusion region on 8 September 2015 (Eriksson, Wilder, et al, ) were found to be in good agreement with numerical simulation results on the basis of Vector Particle‐in‐Cell (VPIC), a 3D fully kinetic particle‐in‐cell code (Bowers et al, , ).…”
Section: Kinetic Particle‐in‐cell Simulation Of Mms Kh Eventmentioning
confidence: 99%
“…Under certain solar wind conditions, the Kelvin‐Helmholtz (KH) instability creates surface waves and vortices along the flanks of the magnetopause as the high velocity solar wind deflects around the magnetosphere and is believed to be an important source of plasma transport during low magnetic field shear (e.g., Hasegawa et al, ; Miura, ; Nakamura, Eriksson, et al, ; Nakamura, Hasegawa, et al, ). It also provides a near‐Earth region for investigating a form of highly driven, strong guide field reconnection referred to as vortex‐induced reconnection (VIR), which has been proposed to occur under northward interplanetary magnetic field along the magnetopause edges of this surface wave (e.g., Liu & Hu, ; Pu, Yan, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation studies from magnetohydrodynamics (MHD) to particle-in-cell (PIC) simulation show a large range of transport rates from 10 9 to 10 10 m 2 /s for Earth's magnetopause environments (Cowee et al, 2009(Cowee et al, , 2010Delamere et al, 2011;Miura, 1984;Ma et al, 2017;Nykyri & Otto, 2001, 2004Nakamura et al, 2017). Simulation studies from magnetohydrodynamics (MHD) to particle-in-cell (PIC) simulation show a large range of transport rates from 10 9 to 10 10 m 2 /s for Earth's magnetopause environments (Cowee et al, 2009(Cowee et al, , 2010Delamere et al, 2011;Miura, 1984;Ma et al, 2017;Nykyri & Otto, 2001, 2004Nakamura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%